أثر القيادة التحويلية على أداء العاملين في المعاهد العليا: دراسة ميدانية بمنطقة البطنان (Comprehensive Journal of Science, 2025)
This study aims to explore the impact of transformational leadership on the performance of employees in higher education institutions in the Al-Batinah region, with a focus on academic and administrative aspects. The study adopted a descriptive analytical approach due to its suitability for the nature of the study, and data was collected using a questionnaire distributed to a sample of 108 academics and administrators in five higher education institutions. The results showed that transformational leadership has a highly positive effect on raising job performance, with a correlation coefficient of 0.72, and that 0.52 of the job performance level is attributable to transformational leadership. The study indicates that adopting transformational leadership practices is an effective way to improve the overall performance of employees and enhance the quality of education in higher education institutions. The study also recommends the need to organize training programs to enhance leaders' skills in the areas of effective communication, change management, and technology, as these are essential components of transformational leadership, with the aim of raising performance levels and achieving a more efficient and effective learning environment.
Keywords: Transformational Leadership – Employees’ Performance – Higher Institutes